(untitled) (Pedagogy of Higher and Secondary Education, 2022)
This article deals with the questtion about the youth clubs in out of school education and upbringing teenagers. With the help of the work o f youth cluds there is one more possibility of development pupils abilities, including them info the system of recearching and creative activity.